Russians in Ukrainian Folklore from the 20th and Early 21st Centuries: The Dynamics of the Images and Contexts - Kuzmenko, Oksana (Tautosakos darbai, 2022)
The article presents the genesis and dynamics of the ethnostereotype of Russians in Ukrainian folklore from the 20th and early 21st centuries. The object of the interdisciplinary research is texts from printed sources, archival collections, and texts recorded during the author’s latest fieldwork between 2013 and 2018. The subject of the article is the variability of the ethnostereotype and its features. The goal is the semantic-structural analysis of three main images (moskal, ‘executioner [kat]’, rashyst), the main meaning of which is ‘invader of Ukrainian land’. Based on materials of various genres and the contexts of their functioning, the author proves that the image of the moskal was the most common in the folklore of the First World War. It preserves the archaic semantics of ‘devil’ and ‘alien’ based on folklore models from the 19th century. The image is ambivalent, mainly with negative connotations (uneducated, cunning, treacherous, thieving, rapacious, aggressive, cruel). The emphasis is placed on role changes in the semantics of the image of the enemy, the transition from ‘animal’ to human’. The change was fixed by the opposition in the formula ‘first’ (not) second moskal. The author examines the image of the ‘executioner’ based on the motifs of violence, cruelty and revenge highlighted in the insurgent and eviction folklore which formed during the Second World War. It is emphasised that in the folklore formula ‘Moscow executioner’, one should understand the superiority of the national over the social. The conclusions state that the semantics of the new images of Russians (rashyst, ork, rusnia) and their meaning are determined by the modern context of the Russian-Ukrainian war and the previously formed stereotypical meanings of moskal. Constant metaphorical epithets (‘scary’, ‘dark’ as uneducated, ‘wild’, ‘vile’, ‘lying’, ‘dirty’, ‘evil’, ‘fierce’, ‘Red’) verbalise these meanings.